Elemen-Elemen Sebagai Acuan Untuk Menemukan Arah Dan Tempat (Way-Finding) Di Dalam Kompleks Bangunan : Kajian Empiris Pada Kasus RSUP Dr. Sardjito, Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
General-hospital building is a setting that requires easiness in way-finding, especially for visitors who are not familiar with the hospital environment. One of the important factor that support easiness in way-finding is the existence of visual reference. This research aims at identifying the physical elements that are memorized by the visitors when they walk toward a place at RSUP Dr. Sardjito Hospital, Yogyakarta, and examining the characteristics of these elements. Thirty hospital visitors participated in this study. Primary data are gathered by several methods namely observation, structured interview, behavior mapping, and cognitive map sketching. The way-finding activities performed by the hospital visitors consist of several stages and have a specific pattern of movement based on the destination zone. Four types of elements, used as the way-finding reference by the visitors, are: area, point of activity, element of circulation, and element in space. These four elements are closely related to the condition of environment in which visitors are used to do their activities and to their level of interaction with that environment. The clear boundary area, existence of movement as a place marker, and contrast of color and form with the surrounding environment, are physical characteristics which indicate that the elements of way-finding reference have qualities to be easily identified (identifiability) and easily distinguished (distinctiveness). The strategic locations on primary circulation lanes and major decision points, indicate that the elements of way-finding reference have also a quality to be easily seen (visibility).